Analytic hierarchy process in purchasing import and local car models among first time car buyers in Malaysia - Mohamad Arisa, Nur Syazwani Aqilah; Che Him, Norziha; Rusiman, Mohd Saifullah (2021)
An automotive industry in Malaysia contributed to the huge success in economic development. This study aims to investigate various factors that could affect the decision before deciding and purchasing a car as the first owner in Malaysia. The factors chosen have been considered by using Analytic Hierarchy Process (AHP). This study could categorise as useful guideline for the first time car buyer and for automotive industry in Malaysia to seize challenges and further opportunities in preparing the first class service to customers. Besides, this study purpose is to identify the demography of respondents and most priority factors that could influenced car buyer to purchase a local and import car by using AHP. A total of 85 respondents have involved in this study, 72% consist of female and 28% of them are male. Besides, 49 of them have their own car and mostly buy their first car at the range age of 20-25 years' old. Results shows that the most priority criteria preferred the first time car are performance followed by safety system, economic aspect, technology, brand, after sales service and exterior where they present highest preference in performance as that is most important factor need to be considered before purchasing a car.